Advances in power system modelling, control and stability analysis - Milano, Federico (IET power and energy series, 2016)
This book describes the variety of new methodologies and technologies that are changing the way modern electric power systems are modelled, simulated and operated. It mixes theoretical aspects with practical considerations, as well as benchmarks test systems and real-world applications.